ANALISIS PENERAPAN PENDEKATAN SAINTIFIK PADA PEMBELAJARAN TEMATIK INTEGRATIF (Studi pada Guru Kelas III SDN Prawit 1 Surakarta) - ILYAS SAZALLY ROSYIDI; Lydia Ersta Kusumaningtyas; Ratna Widyaningrum (Widya Wacana: Jurnal Ilmiah, 2021)
The objectives of this study were to determine: 1) The integrated thematic learning process in class III SDN Prawit 1 Surakarta, 2) The application of the scientific approach to integrative thematic learning, 3) The teacher's strategy in overcoming the difficulties of using the scientific approach in integrative thematic learning in class III SDN Prawit 1 Surakarta. This type of research is a qualitative descriptive study. The subjects of this study were Class III teachers at SDN Prawit 1 Surakarta. Data collection methods in this study are through interviews, documentation, and literature study. Interviews are used to get the information needed. The results of this study are: (1) Overall, class III teachers of SD Negeri 1 Surakarta, in compiling a lesson plan (RPP) are appropriate. The teacher first classifies the material according to the aspects of scientific skills that will be trained on students in the preparation of lesson plans (RPP). (2) Learning with a scientific approach has been running in class III at Prawit 1 State Elementary School, Surakarta. Class teachers always try to practice 5M scientific skills (Observing, Asking, Gathering information, Associating, and Communicating). (3) The teacher's strategy in implementing integrative thematic learning activities in class III in order to overcome existing difficulties, requires appropriate supporting factors and strategies, so that learning objectives can be achieved.